Subgenic Pol II interactomes identify region‐specific transcription elongation regulators - Kevin M Harlen; L Stirling Churchman (Molecular Systems Biology)
Abstract Transcription, RNA processing, and chromatin‐related factors all interact with RNA polymerase II (Pol II) to ensure proper timing and coordination of transcription and co‐transcriptional processes. Many transcription elongation regulators must function simultaneously to coordinate these processes, yet few strategies exist to explore the complement of factors regulating specific stages of transcription. To this end, we developed a strategy to purify Pol II elongation complexes from subgenic regions of a single gene, namely the 5′ and 3′ regions, using sequences in the nascent RNA. Applying this strategy to Saccharomyces cerevisiae, we determined the specific set of factors that interact with Pol II at precise stages during transcription. We identify many known region‐specific factors as well as determine unappreciated associations of regulatory factors during early and late stages of transcription. These data reveal a role for the transcription termination factor, Rai1, in regulating the early stages of transcription genome‐wide and support the role of Bye1 as a negative regulator of early elongation. We also demonstrate a role for the ubiquitin ligase, Bre1, in regulating Pol II dynamics during the latter stages of transcription. These data and our approach to analyze subgenic transcription elongation complexes will shed new light on the myriad factors that regulate the different stages of transcription and coordinate co‐transcriptional processes.